2014
DOI: 10.1097/bor.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

New autoantibody detection technologies yield novel insights into autoimmune disease

Abstract: Purpose of review The purpose of this review is to highlight recent progress in autoantibody detection technologies and describe how these methods are providing novel information and insights into autoimmune disorders. Recent findings In recent years, alternative methods such as comprehensive phage display, fluid-phase immunoassays, and antigen microarrays have been developed for autoantigen discovery and profiling autoantibody responses. Compared to classic approaches such as Western blot and ELISA, these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Changes in B and T-cell repertoires have been associated with autoimmune disease, infectious disease, and cancer (Woodsworth et al, 2013). In many cases, specific serological signatures have been shown to be predictive of disease status, for example the detection and abundance of autoantibodies against pancreatic antigens are predictive of type 1 diabetes (Burbelo and O’Hanlon, 2014). The development of autoantibodies generally precedes the development of overt autoimmune disease (Arbuckle et al, 2003), suggesting that early detection of autoantibodies, especially in individuals at high genetic risk for autoimmune disease, could facilitate the early identification of individuals progressing from a healthy to diseased state – providing a window for preventative therapy.…”
Section: High Definition Preventionmentioning
confidence: 99%
“…Changes in B and T-cell repertoires have been associated with autoimmune disease, infectious disease, and cancer (Woodsworth et al, 2013). In many cases, specific serological signatures have been shown to be predictive of disease status, for example the detection and abundance of autoantibodies against pancreatic antigens are predictive of type 1 diabetes (Burbelo and O’Hanlon, 2014). The development of autoantibodies generally precedes the development of overt autoimmune disease (Arbuckle et al, 2003), suggesting that early detection of autoantibodies, especially in individuals at high genetic risk for autoimmune disease, could facilitate the early identification of individuals progressing from a healthy to diseased state – providing a window for preventative therapy.…”
Section: High Definition Preventionmentioning
confidence: 99%
“…Moreover, disorders of the immune system may lead to autoimmune diseases. Multiple AAbs that are specific to autoimmune disease have been found, including thyroiditis, type 1 diabetes mellitus and primary biliary cirrhosis, indicating the contribution of AAbs to pathology by inflammatory stimulation (57). …”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, studies have shown that autoantibodies are present years before clinical symptoms and can be used to predict who might develop autoimmune conditions, including systemic lupus erythematosus (SLE), type I diabetes mellitus (T1D), and Sjögren’s syndrome (SS) [911]. Lastly, due to recent advances in high-throughput immunoassay detection of autoantibodies [12], it is possible to further categorize autoimmune diseases into subclasses based on the presence and levels of autoantibodies directed against different autoantigens demonstrating the utility of these measurements [1316]. …”
Section: Introductionmentioning
confidence: 99%